THE INFLUENCE OF AUTHORITY AND COMPETENCY TO THE WORK COMMITMENT OF ASN EMPLOYEES AT THE KAMPAR DISTRICT HEALTH OFFICE - Wan Yafi’ah Mudrikah; Zamhir Basem; Muhammad Salis (Jurnal Riset Manajemen Indonesia, 2021)
This research has been carried out and aims to determine the effect of authority and competence simultaneously and partially on the work commitment of ASN employees at the Kampar district health office. Sampling was done by using the slofin formula method from a population of 105 to 52 respondents. Data analysis was performed by multiple linear regression. Based on the test results simultaneously and partially, the variables of authority and competence have a significant effect on the work commitment of ASN employees at the Kampar District Health Service. The closeness of the relationship between the independent variables (authority and competence) and the dependent variable (work commitment) ASN employees is strong with the correlation coefficient (R) of 86.9%, while the contribution (R2) of the independent variable to the dependent variable is 75.6% ( very high), while the remaining 24.4% is influenced by other variables not examined in this study.